KEUNGGULAN KOMPARATIF BAMBU SEBAGAI BAHAN ALTERNATIF PENGGANTI BAHAN BAKU UNTUK KELOMPOK INDUSTRI KERAJINAN DI WONOREJO PASURUAN - Dayanti, Arum Dwi; Abror, Ulul (Jurnal Ilmu Manajemen Advantage, 2018)
Managing the viability of small businesses in small industry groups requires carefulness and special ability, especially when the business actor faces the scarcity of raw materials used in the production process. As the researchers face in the survey on the parcel craftsmen group, which used to use rattan material has now switched to using bamboo materials in maintaining the continuity of production in the region Wonorejo Pasuruan. Parcel craftsmen groups in this area until now amounted to 33 craftsmen who have largely switched to using bamboo materials as the main ingredient of making the parcel. With the use of bamboo materials that are easier in the business can be maintained well maintained.